Protoplast Isolation and Regeneration from Gracilaria changii (Gracilariales, Rhodophyta) - Yeong, Hui Yin; Khalid, Norzulaani; Phang, Siew Moi (2008)
The tropical agarophyte Gracilaria changii has been much researched and documented by the Algae Research Laboratory, University of Malaya, especially with regards to its potential as a seaweed bioreactor for valuable compounds. Protoplast regeneration of this seaweed was developed following the optimization of protoplast isolation protocol. Effect of the concentration and combination of isolating enzymes, incubation period, temperature, enzyme solution pH, tissue source on the protoplast yields were used to optimize the isolation protocol. The enzyme mixture with 4 w/v cellulase Onozuka R-10, 2 w/v macerozyme R-10 and 1 unit mL-1 agarase was found to produce the highest yield of protoplast at 28Â°C and 3 h incubation period. Thallus tips gave higher yields of protoplasts than middle segments. Freshly isolated G. changii protoplasts were cultured in MES medium. Regeneration of protoplast cell walls after 24 h was confirmed by calcofluor white M2R staining under UV fluorescence microscopy. The protoplasts with regenerated cell walls then underwent a series of cell division to produce callus-like cell masses in MES medium. Following this, juvenile plants of G. changii were obtained.